Lactobacillus probiotic cell-free supernatants and vitamin D influence interleukin-6 production and mitigate oral periodontopathogens-induced cytotoxicity in FaDu cells - Zanetta, Paola; De Giorgis, Veronica; Barberis, Elettra; Manfredi, Marcello; Amoruso, Angela; Pane, Marco; Azzimonti, Barbara (Frontiers in Microbiology, 2025)
Oral eubiosis is of utmost importance for local and systemic health. Consolidated habits, as excessive alcohol consumption, smoke, inappropriate oral hygiene, and western diet, exert detrimental effects on oral microbiota composition and function. This leads to caries, gingivitis, and periodontitis, also increasing the risk of preterm births, inflammation, and cancer. Thus, effective tools to contain pathobiont overgrowth and virulence and restore oral eubiosis are needed. Therefore, the effects of Limosilactobacillus reuteri LRE11, Lacticaseibacillus rhamnosus LR04, Lacticaseibacillus casei LC04, and their co-culture cell-free supernatants (CFSs), produced in both conventional MRS medium and a novel animal derivative-free medium named TIL, along with vitamin D, were assessed on the viability and interleukin (IL)-6 production of oral epithelial FaDu cells infected with Aggregatibacter actinomycetemcomitans, Fusobacterium nucleatum, and Porphyromonas gingivalis. The CFS proteomic, short chain fatty acid, and lactic acid contents were also investigated. Interestingly, probiotic CFSs and vitamin D differentially reduced the infected cell IL-6 production and counteracted the infection-induced cytotoxicity. Taken together, these results suggest that probiotics and vitamin D can reverse pathogen-induced cell damage. Since probiotic CFS effect is both strain and growth medium composition dependent, further experiments are required to deepen the probiotic and vitamin D synergic activity in this context.